2019
DOI: 10.1016/j.tcs.2018.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Recursive stochastic games with positive rewards

Abstract: We study the complexity of a class of Markov decision processes and, more generally, stochastic games, called 1-exit Recursive Markov Decision Processes (1-RMDPs) and 1-exit Recursive Simple Stochastic Games (1-RSSGs), with strictly positive rewards. These are a class of finitely presented countable-state zero-sum turn-based stochastic games that subsume standard finitestate MDPs and Condon's simple stochastic games. They correspond to optimization and game versions of several classic stochastic models, with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In [7], it was shown that the approximation of the optimal probability of extinction for BMDPs can be done in polynomial time. The computational complexity of computing the optimal expected total cost before extinction for BMDPs follows from [8] and was shown there to be computable in polynomial time via a linear program formulation. The problem of maximising the probability of reaching a state with an entity of a given type for BMDPs was studied in [6].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7], it was shown that the approximation of the optimal probability of extinction for BMDPs can be done in polynomial time. The computational complexity of computing the optimal expected total cost before extinction for BMDPs follows from [8] and was shown there to be computable in polynomial time via a linear program formulation. The problem of maximising the probability of reaching a state with an entity of a given type for BMDPs was studied in [6].…”
Section: Related Workmentioning
confidence: 99%
“…Following [8], we define here a linear equation system with a minimum operator whose Least Fixed Point solution yields the desired optimal values for each type of a BMDP with non-negative costs. This system generalises the Bellman's equations for finite-state MDPs.…”
Section: Fixed Point Equationsmentioning
confidence: 99%
“…Supermodular games always have a pure Nash equilibrium. For related work, see, e.g.,[14,24] or [27, Section 2.1].…”
mentioning
confidence: 99%